ACID PRINCIPLES AND ORACLE'S TRANSACTION MODEL - Fuadov Juratbek, (Ustozlar uchun, 2025)
Transactions are a critical component of modern database systems, ensuring the reliable execution of data operations under various conditions, including concurrent access and system failures. The ACID principles—Atomicity, Consistency, Isolation, and Durability—form the foundation of transactional integrity in relational databases. Oracle Database, as one of the most mature and widely adopted relational database management systems, provides a powerful and finely tuned transaction model that closely follows and enforces the ACID properties. This paper explores how Oracle realizes these principles internally, examines the practical mechanisms and architectural decisions that support them, and highlights their importance for data correctness and reliability.